Potential Climate Change Mitigation Opportunities in Waste Management Sector in Vietnam - RCEE Energy and Environment JSC (World Bank, Washington, DC, 2017)
Along with economic growth and improved living standards, waste from households, industries, and commercial or service establishments is expected to increase rapidly over the next years. Managing this waste is a hard challenge for the Government of Vietnam because of its substantial cost and lack of awareness and participation of people and businesses. Wastes can be classified according to: their form (wastewater, solid waste); their origin (industrial wastes, agricultural wastes, urban (municipal) wastes); and their hazardous nature (non-hazardous or hazardous).